On Research, Creation, and Testing of Devices for Electronic Deployment of Permanent Continuous Analog Visible Recording of Low–Frequency Processes - Mkhitaryan, S. A.; Antonyan, A. P.; Mnatsakanyan, A. R.; Hovhannisyan, M. A.; Chilingaryan, R. Y.
Mechanical methods of deployment of permanent, continuous analog visible recording of signals complicate the design of analog recorders and light–beam oscilloscopes with the continuous visible recording of low–frequency processes and periodic output of recording frames, reduce their reliability and accuracy, make it difficult to adjust deployment steps, increase power and dimensions, and also lead to additional geometrical and optical errors in light–beam oscilloscopes. To eliminate these shortcomings, electronic methods for deployment of continuous analog visible recording are proposed and analysed, on the basis of which corresponding devices are also developed, created, and tested, with the help of which the proposed electronic methods are tested and verified based on ASEO type Automatic seismic electrographic oscilloscopes.
Keywords: Physics